(untitled) (Cadernos de Sociomuseologia, 2014)
The central focus in this research is the communication between museums and the its audience. I start at the hypothesis that communication is an essential factor to make the integration among the museum´s audience, its patrimony and the museum itself easier. Such integration, consequently, influences the educational process. Starting at this point, I suggest the main hypothesis, according to it, in the soccer museums the communication between the institution and its audience is more efficient because the same referential occurs in the Brazilian soccer rooter community and the Brazilian individuals what does not occurs in the other museum kinds or another patrimony kinds. The relevance of this study for the society lies in the contribution for the improvement on the services afforded by the museums. In first place, I make a study about the communication developed by the museums through its hanging out narratives. In second place, there are analyzed the profiles of the audience of the different kinds of museums. In the end, I evaluate the communication process between museums and its audience, where are observed aspects as professionalism, media publicizing, ludicity, frequency and preferences of the audience. Although all this elements are important, the study points that a presentation of a common language between the museum and the public, as happens in soccer’s museums, is essential for a better communication. Finally, for hypothesis confirmation, I accomplish an analysis of speech of the announcements and texts related to educational projects, verifying also their reflect on the relationship with the public. Keywords: Museums, Education, Soccer, Identity, Communication.